Assessment of myocardial repolarisation parameters in patients with familial Mediterranean fever - Karaman, Kayıhan (Cardiovasc J Afr, 2017)
BACKGROUND: Familial Mediterranean fever (FMF) is a chronic, recurrent auto-inflammatory disease characterised by self-terminating attacks of fever and sterile polyserositis. The main cause of death in auto-inflammatory diseasesis cardiovascular events. Additionally, auto-inflammatory diseases have potential effects on the myocardial repolarisation parameters, including the T-wave peak-to-end (Tp-Te) interval, cTp-Te interval (corrected Tp-Te) and the cTp-Te/ QT ratio. The aim of this study was to analyse the efficacy of myocardial repolarisation alterations in anticipation of cardiovascular risks in patients with FMF. METHODS: This study included 66 patients with FMF and 58 healthy control subjects. Tp-Te and cTp-Te intervals and the cTp-Te/QT ratio were measured from the 12-lead electrocardiogram. RESULTS: In electrocardiographic parameters, analysis of QT, QT dispersion, corrected QT (QTc) and QTc dispersion were similar between the groups. The Tp-Te and cTp-Te intervals and Tp-Te/QT and cTp-Te/QT ratios were significantly prolonged in FMF patients. Multivariate linear regression analyses indicated that erythrocyte sedimentation rate was an independent predictor of a prolonged cTp-Te interval. CONCLUSIONS: Our study revealed that when compared with control subjects, Tp-Te and cTp-Te intervals and cTp-Te/QT ratio were increased in FMF patients.